Analisis Percepatan (AI) Dan Kemampuan Berpikir Terhadap Optimalisasi Penyelesaian Tugas Akademik Mahasiswa Universitas Muhammadiyah Mamuju - Putri, Devita Arista; Akbar, Muh; Yeni, Hari (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
The development of Artificial Intelligence (AI) technology in the education sector has driven significant changes in the learning process, particularly in supporting the efficiency and quality of students’ academic task completion. This study aims to analyze the influence of AI acceleration and students’ thinking abilities on the optimization of academic task completion at the University of Muhammadiyah Mamuju. The coefficient of determination (R²) value of 0.415 indicates that 41.5% of the variation in academic task optimization is influenced by these two variables. Data analysis was conducted using SPSS version 25 to test the research instruments and hypotheses. The results of the instrument testing indicate that all statement items are valid and reliable, with Cronbach’s Alpha values exceeding 0.60. The normality test using the Kolmogorov–Smirnov method produced a significance value of 0.200, indicating that the data are normally distributed. The multiple linear regression analysis resulted in the equation Y = 3.437 + 0.339X₁ + 0.238X₂. Partially, the AI Acceleration variable has a significant effect (Sig. 0.002), and Thinking Ability also has a significant effect (Sig. 0.027) on the dependent variable. These findings confirm that although accelerated AI utilization can enhance the efficiency of academic task completion through automation, critical thinking skills remain a key factor in maintaining the quality of academic output and minimizing the risk of academic laziness.